Tear-resistant fluororubber material and preparation method thereof

By modifying the compatibility of carbon nanotubes and fluoroelastic rubber, the tear resistance and mechanical properties of fluoroelastic rubber are significantly improved, and its flame retardant properties are improved, solving the problem of performance degradation of fluoroelastic rubber in high and low temperature environments.

CN119708731AInactive Publication Date: 2025-03-28NINGBO YOKEY PRECISION TECH CO LTD

Patent Information

Application Number
CN202510225517.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The performance of existing fluoroelastomers is degraded in high-temperature environments, which is prone to thermal tear, and is easily damaged when used in low-temperature environments. The compatibility of carbon nanotubes and fluoroelastomers is poor, affecting their tear resistance.

Method used

By preparing modified carbon nanotubes, it includes adding multi-walled carbon nanotubes to butane 2-phosphonate-1,2,4-tricarboxylic acid for modification, then adding phosphonic acid modified carbon nanotubes and thioacetamide to pure water, adding metal nitrate after ultrasonic stirring, and further modifying the carbon nanotubes to improve their compatibility with fluoroelastomer.

Benefits of technology

It significantly improves the tear resistance of fluoroelastomer (tear strength up to 45.5~47.3kN/m) and mechanical properties, and also improves its flame retardant properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a tear-resistant fluororubber material and a preparation method thereof, and belongs to the technical field of fluororubber production, and the tear-resistant fluororubber material comprises the following raw materials: tetrafluoroethylene-propylene rubber, modified carbon nanotubes, a vulcanizing agent, an accelerant, a plasticizer and an anti-aging agent. The modified carbon nanotube is prepared by the following steps: adding a multi-walled carbon nanotube into 2-phosphonobutane-1, 2, 4-tricarboxylic acid, vacuumizing, heating and stirring, cooling, discharging, washing and drying to obtain a phosphonic acid modified carbon nanotube, adding the phosphonic acid modified carbon nanotube and thioacetamide into pure water, ultrasonically stirring, adding a metal nitride, and stirring to obtain the phosphonic acid modified carbon nanotube. And heating to 80-90 DEG C, stirring at a constant temperature for 8-10 hours, cooling to room temperature after the stirring is finished, and carrying out suction filtration, washing and drying to obtain the modified carbon nanotube. Through detection, the fluororubber prepared by the invention has excellent tear resistance, mechanical property and flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluororubber production, and in particular relates to a tear-resistant fluororubber material and a preparation method thereof. Background Art

[0002] Fluororubber is a synthetic polymer elastomer containing fluorine atoms on the carbon atoms of the main chain or side chain. Due to its excellent high temperature resistance, chemical corrosion resistance, and aging resistance, it is widely used in aerospace, shipbuilding, automobiles, petroleum machinery, chemical industry, electronic information and other fields.

[0003] Fluororubber has obvious advantages, but its performance will seriously degrade in high temperature environment, causing fluororubber products to easily produce thermal tearing during demolding, be easily damaged when used at high temperature, and also be damaged when used in low temperature environment.

[0004] In order to improve the tear resistance of fluororubber, many improvements have been made in the prior art. For example, the invention patent with application number 201510797261.5 discloses a tear-resistant fluororubber compound and a preparation method thereof. This invention addresses the problem of poor tear performance of fluororubber by adding carbon nanotubes to fluororubber to prepare a fluororubber with improved tear strength. After testing, the crescent tear strength of the fluororubber prepared by this invention reaches 41kN / m.

[0005] However, carbon nanotubes have high surface energy and chemical inertness, and their surface is mainly composed of carbon atoms, while the fluororubber substrate is a fluorine-containing polymer material with a large number of fluorine atoms in the molecular chain. The huge difference in the surface properties of carbon nanotubes and the fluororubber substrate leads to poor compatibility between them. The high fluorine content of the fluororubber molecular chain makes it highly hydrophobic, and the non-polarity of the carbon nanotube surface also makes it lack sufficient mutual attraction with the fluororubber, which is prone to phase separation. Therefore, it is necessary to improve the carbon nanotubes, improve the compatibility of carbon nanotubes and fluororubber, and ultimately further improve the tear resistance of fluororubber. Summary of the invention

[0006] The object of the present invention is to provide a tear-resistant fluororubber material and a preparation method thereof, so as to further improve the tear-resistant performance of the fluororubber.

[0007] The purpose of the present invention can be achieved through the following technical solutions: A tear-resistant fluororubber material, comprising the following raw materials in parts by weight: 100 parts of tetrafluoroethylene rubber; 15-20 parts of modified carbon nanotubes; 1 to 3 parts of vulcanizing agent; 0.2-2 parts of accelerator; 10-15 parts of plasticizer; 1 to 3 parts of antioxidant; The modified carbon nanotubes are prepared by the following steps: S1, adding multi-walled carbon nanotubes to 2-phosphonobutane-1,2,4-tricarboxylic acid, evacuating, heating to 60-65°C, stirring at constant temperature for 12 hours, then heating to 120-130°C, stirring at constant temperature for 4-5 hours, cooling, discharging, washing and drying to obtain phosphonic acid modified carbon nanotubes; S2. Add phosphonic acid-modified carbon nanotubes and thioacetamide into pure water, add metal nitrate after ultrasonic stirring, raise the temperature to 80-90°C, stir at constant temperature for 8-10 hours, cool to room temperature, filter, wash and dry to obtain modified carbon nanotubes.

[0008] Furthermore, the usage ratio of 2-phosphonobutane-1,2,4-tricarboxylic acid and multi-walled carbon nanotubes in S1 is 1L:20-30g.

[0009] Furthermore, the usage ratio of pure water, phosphonic acid-modified carbon nanotubes, thioacetamide and metal nitrate in S2 is 200 mL: 20 g: 1.5 g: 5.5-6.0 g.

[0010] Furthermore, the metal nitrate is one of zinc nitrate, aluminum nitrate and magnesium nitrate.

[0011] Furthermore, the vulcanizing agent is bisphenol AF or dicumyl peroxide.

[0012] Furthermore, the accelerator is benzyltriphenylphosphonium chloride.

[0013] Furthermore, the plasticizer is one of dibutyl phthalate, dioctyl adipate and tricresyl phosphate.

[0014] Furthermore, the antioxidant is one of antioxidant 6PPD, antioxidant TMQ and antioxidant IPPD.

[0015] Furthermore, a method for preparing a tear-resistant fluororubber material comprises the following steps: Weigh the raw materials according to the mass proportion, and then set the roller temperature of the open mill to 45-50°C. After the temperature is raised, place the tetrapropylene fluororubber in the open mill for plasticization for 3-4 minutes. After the temperature is raised, add the modified carbon nanotubes, vulcanizer, accelerator, plasticizer and antioxidant to the open mill. After the addition is completed, after the rubber material is completely powdered, cut the rubber on the left and right sides for 4-5 times, then make triangle packages 2-4 times in turn, then roll it 2-4 times, and then thin it 4-5 times. After the completion, discharge the material to obtain a mixed rubber, and then place the mixed rubber on a flat vulcanizer for a first-stage vulcanization to obtain a film, and then transfer the film to an aging box for a second-stage vulcanization. After the second-stage vulcanization is completed, take it out and cool it to room temperature to obtain a tear-resistant fluororubber material.

[0016] Furthermore, the vulcanization conditions of the first stage vulcanization are 175-177°C / 15MPa×20min; and the vulcanization conditions of the second stage vulcanization are 200-210°C×4h.

[0017] Beneficial effects of the present invention: The present invention provides a fluororubber material and a preparation method thereof. According to tests, the prepared fluororubber has excellent tear resistance (tear strength of 45.5-47.3 kN / m) and mechanical properties (tensile strength and elongation at break). The present invention significantly improves the tear resistance of the fluororubber by adding self-made modified carbon nanotubes, wherein the modified carbon nanotubes are prepared by modifying carbon nanotubes with phosphonic acid and then carrying metal elements (zinc / aluminum / magnesium). First, the principle of phosphonic acid-modified carbon nanotubes is as follows: (1) Improve interface bonding strength: a. Chemical bonding: The phosphate in the organic phosphonic acid forms a covalent bond with the hydroxyl and carboxyl groups on the surface of the carbon nanotubes. At the same time, the organic part of the organic phosphonic acid produces a van der Waals force with the fluorine atoms in the fluororubber molecular chain, thereby forming a dual effect of chemical bonding and physical adsorption between the carbon nanotubes and the fluororubber, enhancing the interfacial bonding force between the two, and ultimately improving the tear resistance of the prepared fluororubber.

[0018] b. Increase surface roughness: Organic phosphonic acid increases the surface roughness of carbon nanotubes. When carbon nanotubes come into contact with fluororubber, the rough surface can better fit and mechanically interlock with the rubber molecules, thereby improving the stability and bonding strength of the interface.

[0019] (2) Improve dispersibility: a. Reduce surface energy: Carbon nanotubes have high surface energy and are easy to agglomerate. After organic phosphonic acid molecules are adsorbed on the surface of carbon nanotubes, their surface energy can be reduced, and the mutual attraction between carbon nanotubes is weakened, thereby effectively preventing the agglomeration of carbon nanotubes and making them easier to disperse evenly in the fluororubber matrix.

[0020] b. Steric hindrance effect: The molecular chain of organic phosphonic acid has a certain length and spatial volume. When attached to the surface of carbon nanotubes, it will produce steric hindrance between carbon nanotubes, preventing the carbon nanotubes from approaching each other and agglomerating, which is beneficial for the carbon nanotubes to be dispersed in the fluororubber in the form of single or smaller aggregates, thereby improving the interaction between carbon nanotubes and fluororubber.

[0021] Then, the principle of carrying metal elements (zinc / aluminum / magnesium) is as follows: The metal nitrate will be ionized to produce metal cations and nitrate ions. The metal cations will react with the phosphonic acid groups on the surface of the phosphonic acid modified carbon nanotubes, thereby introducing metal ions (zinc ions / aluminum ions / magnesium ions) on the surface of the carbon nanotubes. Among them, the metal zinc ions / aluminum ions / magnesium ions can form coordination, complexation and ionic bonds with the fluorine atoms in the fluororubber molecular chain, respectively, thereby enhancing the interface bonding force between the prepared modified carbon nanotubes and the fluororubber. When the fluororubber is subjected to external force, the carbon nanotubes can better transmit stress and are not easy to be pulled out or slide from the rubber matrix, making it difficult for the tear crack to expand, thereby improving the tear resistance of the fluororubber. Among them, zinc ions can induce the crystallization of fluororubber during the vulcanization process of fluororubber, increase the crystallinity of fluororubber, and the crystallized area can be used as a physical crosslinking point to enhance the overall strength and modulus of the rubber. At the same time, it can also hinder the propagation of tear cracks, thereby improving the tear resistance.

[0022] At the same time, adding the modified carbon nanotubes prepared by the present invention can improve the flame retardant properties of the prepared fluororubber, and the specific principle is as follows: (1) Effect of phosphonic acid modification stage (S1) on flame retardant properties: a. Forming a carbon layer: In step S1, 2-phosphonobutane-1,2,4-tricarboxylic acid is used to modify the multi-walled carbon nanotubes. The phosphonic acid group can decompose at high temperature to produce acidic substances such as phosphoric acid. These acidic substances can catalyze the dehydration and carbonization of the fluororubber surface and promote the formation of a dense carbon layer. This carbon layer can prevent heat and oxygen from transferring to the interior of the fluororubber, thereby inhibiting the further development of combustion.

[0023] b. Free radical capture: The phosphorus-containing free radicals produced by the decomposition of phosphonic acid can also capture hydrogen free radicals and hydroxyl free radicals during the combustion process in the gas phase, thereby reducing the combustion rate and playing a flame retardant role.

[0024] (2) Effect of metal ion introduction stage (S2) on flame retardant properties: a. Formation of metal oxides: When metal nitrates (zinc nitrate hexahydrate, aluminum nitrate nonahydrate or magnesium nitrate hexahydrate) are added, the metal nitrates will decompose to produce metal ions during the reaction process. During the combustion process, these metal ions will react with oxygen in the air or oxygen produced by the combustion of fluororubber to form metal oxides. Metal oxides can act as a physical barrier to cover the surface of fluororubber, preventing direct contact between flames and fluororubber, and can absorb heat, play a role in heat insulation, and slow down the combustion rate.

[0025] b. Synergistic flame retardant effect: Metal oxides and the carbon layer formed by the previous phosphonic acid modification can produce a synergistic flame retardant effect. The carbon layer can prevent the transfer of oxygen and heat, and the metal oxide on the surface of the carbon layer further enhances this barrier effect. At the same time, the metal oxide can also react with acidic gases such as hydrogen halides (which may be produced by the combustion of fluororubber) produced during the combustion process, reduce the release of acidic gases, and stabilize the carbon layer structure, making it denser, further improving the flame retardant performance. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] Example 1 Preparation of modified carbon nanotubes: S1. Add 2-phosphonobutane-1,2,4-tricarboxylic acid (purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and multi-walled carbon nanotubes (purity ≥ 95%, inner diameter: 5-12 nm, outer diameter: 30-50 nm, length: 20 μm, specific surface area: >300 m) into reactor a with stirring. 2 / g; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.), wherein the amount ratio of 2-phosphonobutane-1,2,4-tricarboxylic acid and multi-walled carbon nanotubes is 1L:25g. After the addition is completed, the reactor a is evacuated, and then the temperature is raised to 60°C, and the reaction is stirred at a constant temperature for 12h. After the reaction is completed, the reactor a is heated to 120°C again, and the reaction is stirred at a constant temperature for 4h. After the reaction is completed, it is cooled to room temperature, discharged, and the product is washed three times with pure water, filtered under reduced pressure, and the solid component is collected. It is placed at a constant temperature of 40°C and dried to constant weight to obtain phosphonic acid modified carbon nanotubes; S2. Pure water, phosphonic acid-modified carbon nanotubes and thioacetamide (purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) are added to reactor b with stirring. After the addition is completed, ultrasonic stirring is performed for 20 minutes. After the addition is completed, aluminum nitrate nonahydrate (purchased from Sinopharm Chemical Reagent Co., Ltd.) is added to reactor b with stirring. The amount ratio of pure water, phosphonic acid-modified carbon nanotubes, thioacetamide and aluminum nitrate nonahydrate is 200mL:20g:1.5g:5.5g. After the addition is completed, the temperature of reactor b is raised to 80°C, and the reaction is stirred at a constant temperature for 8 hours. After the completion, the reaction is allowed to stand and cool to room temperature. After suction filtration, the solid components are collected, the solid components are washed with pure water, and then placed at a constant temperature of 40°C for drying for 12 hours. After the completion, modified carbon nanotubes are obtained.

[0028] Example 2 Preparation of modified carbon nanotubes: S1. Add 2-phosphonobutane-1,2,4-tricarboxylic acid (purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and multi-walled carbon nanotubes (purity ≥ 95%, inner diameter: 5-12 nm, outer diameter: 30-50 nm, length: 20 μm, specific surface area: >300 m) into reactor a with stirring. 2 / g; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.), wherein the amount ratio of 2-phosphonobutane-1,2,4-tricarboxylic acid and multi-walled carbon nanotubes is 1L:28g. After the addition is completed, the reactor a is evacuated, and then the temperature is raised to 65°C, and the reaction is stirred at a constant temperature for 12h. After the reaction is completed, the reactor a is heated to 125°C again, and the reaction is stirred at a constant temperature for 5h. After the reaction is completed, it is cooled to room temperature, discharged, and the product is washed three times with pure water, filtered under reduced pressure, and the solid component is collected. It is placed at a constant temperature of 40°C and dried to constant weight to obtain phosphonic acid modified carbon nanotubes; S2. Pure water, phosphonic acid-modified carbon nanotubes and thioacetamide (purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) are added to reactor b with stirring. After the addition is completed, ultrasonic stirring is performed for 30 minutes. After the addition is completed, zinc nitrate hexahydrate (purchased from Sinopharm Chemical Reagent Co., Ltd.) is added to reactor b with stirring. The amount ratio of pure water, phosphonic acid-modified carbon nanotubes, thioacetamide and zinc nitrate hexahydrate is 200mL:20g:1.5g:5.8g. After the addition is completed, the temperature of reactor b is raised to 85°C, and the reaction is stirred at a constant temperature for 10 hours. After the completion, the reaction is allowed to stand and cool to room temperature. After suction filtration, the solid components are collected, the solid components are washed with pure water, and then placed at a constant temperature of 40°C for drying for 12 hours. After the completion, modified carbon nanotubes are obtained.

[0029] Example 3 Preparation of modified carbon nanotubes: S1. Add 2-phosphonobutane-1,2,4-tricarboxylic acid (purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) and multi-walled carbon nanotubes (purity ≥ 95%, inner diameter: 5-12 nm, outer diameter: 30-50 nm, length: 20 μm, specific surface area: >300 m) into reactor a with stirring. 2 / g; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.), wherein the amount ratio of 2-phosphonobutane-1,2,4-tricarboxylic acid and multi-walled carbon nanotubes is 1L:30g. After the addition is completed, the reactor a is evacuated, and then the temperature is raised to 65°C, and the reaction is stirred at a constant temperature for 12 hours. After the reaction is completed, the reactor a is heated to 130°C again, and the reaction is stirred at a constant temperature for 5 hours. After the reaction is completed, it is cooled to room temperature, discharged, and the product is washed three times with pure water, filtered under reduced pressure, and the solid component is collected. It is placed at a constant temperature of 50°C and dried to constant weight to obtain phosphonic acid modified carbon nanotubes; S2. Pure water, phosphonic acid-modified carbon nanotubes and thioacetamide (purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) are added to reactor b with stirring. After the addition is completed, ultrasonic stirring is performed for 30 minutes. After the addition is completed, magnesium nitrate hexahydrate (purchased from Sinopharm Chemical Reagent Co., Ltd.) is added to reactor b with stirring. The amount ratio of pure water, phosphonic acid-modified carbon nanotubes, thioacetamide and magnesium nitrate hexahydrate is 200mL:20g:1.5g:6.0g. After the addition is completed, the temperature of reactor b is raised to 90°C, and the reaction is stirred at a constant temperature for 10 hours. After the completion, it is allowed to stand and cool to room temperature, and then filtered to collect the solid components. The solid components are then washed with pure water and then placed at a constant temperature of 50°C for drying for 12 hours. After the completion, modified carbon nanotubes are obtained.

[0030] Example 4 Preparation of tear-resistant fluororubber materials: First, the tear-resistant fluororubber material includes the following raw materials by weight: 100 parts of tetrafluoroethylene rubber; 15 parts of the modified carbon nanotubes prepared in Example 1; 1 part of bisphenol AF; 0.2 parts of benzyltriphenylphosphonium chloride; 10 parts of dibutyl phthalate; 1 part of antioxidant 6PPD; Then, the preparation method of the tear-resistant fluororubber material comprises the following steps: The raw material tetrafluoroethylene rubber (brand name Aflas100s, purchased from Asahi Glass Co., Ltd. of Japan), the modified carbon nanotubes prepared in Example 1, bisphenol AF (purchased from Sigma-Aldrich Trading Co., Ltd.), benzyltriphenylphosphonium chloride (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.), dibutyl phthalate (purchased from Sinopharm Chemical Reagent Co., Ltd.), and antioxidant 6PPD (purchased from Northeast Auxiliary Chemical Co., Ltd.) were weighed according to mass parts, and then the roller temperature of the mixing mill was set to 45°C. After the temperature was raised, the tetrafluoroethylene rubber was placed in the mixing mill and plasticized for 3 minutes. After completion, the modified carbon nanotubes prepared in Example 1 were added to the mixing mill. Carbon nanotubes, bisphenol AF, benzyl triphenyl phosphine chloride, dibutyl phthalate and antioxidant 6PPD are added. After the rubber material is fully powdered, the rubber is cut 4 times on the left and right sides, and then triangle packages are made 2 times, rolls are made 2 times, and thin passes are made 4 times. After completion, the material is discharged to obtain a mixed rubber. The mixed rubber is then placed on a flat vulcanizer for one-stage vulcanization. The vulcanization conditions for the first stage vulcanization are 175℃ / 15MPa×20min. A film is obtained. The film is then transferred to an aging box for a second stage vulcanization. The vulcanization conditions for the second stage vulcanization are 200℃×4h. After the second stage vulcanization is completed, it is taken out and cooled to room temperature to obtain a tear-resistant fluororubber material.

[0031] Example 5 Preparation of tear-resistant fluororubber materials: First, the tear-resistant fluororubber material includes the following raw materials by weight: 100 parts of tetrafluoroethylene rubber; 15-20 parts of the modified carbon nanotubes prepared in Example 2; Bisphenol AF 1-3 parts; Benzyltriphenylphosphonium chloride 0.2-2 parts; 10-15 parts of dioctyl adipate; Anti-aging agent TMQ 1 to 3 parts; Then, the preparation method of the tear-resistant fluororubber material comprises the following steps: The raw material tetrafluoroethylene rubber (brand name Aflas100s, purchased from Asahi Glass Co., Ltd. of Japan), the modified carbon nanotubes prepared in Example 2, bisphenol AF (purchased from Sigma-Aldrich Trading Co., Ltd.), benzyl triphenylphosphonium chloride (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.), dioctyl adipate (purchased from Sinopharm Chemical Reagent Co., Ltd.), and antioxidant TMQ (purchased from Northeast Auxiliary Chemical Co., Ltd.) were weighed according to mass parts, and then the roller temperature of the mixing mill was set to 48°C. After the temperature was raised, the tetrafluoroethylene rubber was placed in the mixing mill and plasticized for 4 minutes. After completion, the modified carbon nanotubes prepared in Example 2 were added to the mixing mill. Carbon nanotubes, bisphenol AF, benzyl triphenyl phosphonium chloride, dioctyl adipate and antioxidant TMQ are added. After the rubber material has been completely powdered, the rubber is cut 5 times on the left and right sides, and then triangle packages are made 4 times, rolls are made 4 times, and thin passes are made 5 times. After completion, the material is discharged to obtain a mixed rubber. The mixed rubber is then placed on a flat vulcanizer for one-stage vulcanization. The vulcanization conditions for the first stage vulcanization are 176℃ / 15MPa×20min. A film is obtained. The film is then transferred to an aging box for two-stage vulcanization. The vulcanization conditions for the second stage vulcanization are 205℃×4h. After the second stage vulcanization is completed, it is taken out and cooled to room temperature to obtain a tear-resistant fluororubber material.

[0032] Example 6 Preparation of tear-resistant fluororubber materials: First, the tear-resistant fluororubber material includes the following raw materials by weight: 100 parts of tetrafluoroethylene rubber; 20 parts of modified carbon nanotubes prepared in Example 3; 3 parts of dicumyl peroxide; Benzyltriphenylphosphonium chloride 2 parts; Tricresyl phosphate 15 parts; 3 parts of antioxidant IPPD; Then, the preparation method of the tear-resistant fluororubber material comprises the following steps: The raw material tetrafluoroethylene rubber (brand name Aflas100s, purchased from Asahi Glass Co., Ltd. of Japan), the modified carbon nanotubes prepared in Example 3, diisopropyl peroxide (purchased from Sigma-Aldrich Trading Co., Ltd.), benzyl triphenylphosphonium chloride (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.), tritolyl phosphate (purchased from Sinopharm Chemical Reagent Co., Ltd.), and antioxidant IPPD (purchased from Northeast Auxiliary Chemical Co., Ltd.) were weighed according to mass parts, and then the roller temperature of the mixing mill was set to 50°C. After the temperature was raised, the tetrafluoroethylene rubber was placed in the mixing mill and plasticized for 4 minutes. After completion, the prepared Example 3 was added to the mixing mill. After the modified carbon nanotubes, dicumyl peroxide, benzyl triphenyl phosphine chloride, tricresyl phosphate and antioxidant IPPD are added, wait until the rubber material has completely absorbed the powder, cut the rubber 5 times on the left and right sides, then make triangle packages 4 times, roll them 4 times, and thin them 5 times. After completion, discharge the material to obtain a mixed rubber, and then place the mixed rubber on a flat vulcanizer for one-stage vulcanization. The vulcanization conditions for the first stage vulcanization are 177℃ / 15MPa×20min to obtain a film, and then transfer the film to an aging box for a second stage vulcanization. The vulcanization conditions for the second stage vulcanization are 210℃×4h. After the second stage vulcanization is completed, take it out and cool it to room temperature to obtain a tear-resistant fluororubber material.

[0033] Comparative Example 1 Comparative Example 1 is the control group of Example 5, in which the modified carbon nanotubes prepared in Example 2 in Example 5 are replaced with raw multi-walled carbon nanotubes (purity ≥ 95%, inner diameter: 5-12 nm, outer diameter: 30-50 nm, length: 20 μm, specific surface area: >300 m 2 / g; purchased from Shanghai MacLean Biochemical Technology Co., Ltd.), the remaining raw materials, raw material amounts and preparation methods were kept consistent with those in Example 5, and a fluororubber material was finally obtained.

[0034] Comparative Example 2 Comparative Example 2 is the control group of Example 5, in which the modified carbon nanotubes prepared in Example 2 in Example 5 are replaced with the phosphonic acid-modified carbon nanotubes prepared in Example 2, and the remaining raw materials, raw material amounts and preparation methods remain the same as in Example 5, and finally a fluororubber material is obtained.

[0035] Comparative Example 3 Comparative Example 3 is the control group of Example 5, in which the modified carbon nanotubes prepared in Example 2 in Example 5 are removed, and the remaining raw materials, raw material amounts and preparation methods are kept consistent with those in Example 5, and finally a fluororubber material is obtained.

[0036] Test Example 1 The fluororubber materials prepared in Examples 4 to 6 and Comparative Examples 1 to 3 were subjected to performance tests. The performance test process is as follows, and the test results are shown in Table 1: Tear strength: refer to GB / T529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber" to measure the tear strength of fluororubber materials.

[0037] Tensile strength: refer to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" to determine the tensile strength and elongation at break of fluororubber materials.

[0038] Flame retardant performance: refer to GB / T10707-2008 "Determination of combustion performance of rubber" to determine the oxygen index and vertical combustion performance (flame retardant grade) of fluororubber materials.

[0039] Table 1 Test results project Example 4 Example 5 Example 6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tear strength (kN / m) 47.5 49.3 48.8 39.7 40.4 35.2 Tensile strength (MPa) 17.4 18.5 18.2 17.5 17.9 15.0 Elongation at break (%) 97.4 86.7 90.2 96.6 91.3 124.1 Oxygen index (%) 65 68 67 55 62 51 Flame retardant grade FV-0 FV-0 FV-0 FV-1 FV-1 FV-2 It can be seen from Table 1 that the fluororubber prepared in Examples 4 to 6 of the present invention has excellent tear resistance, mechanical properties and flame retardant properties. By comparing the data of Example 5 and Comparative Examples 1 to 3, it can be seen that adding the modified carbon nanotubes prepared in the present invention can significantly improve the tear strength and flame retardant properties of the prepared fluororubber.

[0040] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.

[0041] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A tear-resistant fluororubber material, characterized in that: Including the following raw materials by weight: 100 parts of tetrafluoroethylene rubber; 15-20 parts of modified carbon nanotubes; 1 to 3 parts of vulcanizing agent; Accelerator 0.2-2 parts; 10-15 parts of plasticizer; 1 to 3 parts of antioxidant; The modified carbon nanotubes are prepared by the following steps: S1, adding multi-walled carbon nanotubes to 2-phosphonobutane-1,2,4-tricarboxylic acid, evacuating, heating to 60-65°C, stirring at constant temperature for 12 hours, then heating to 120-130°C, stirring at constant temperature for 4-5 hours, cooling, discharging, washing and drying to obtain phosphonic acid modified carbon nanotubes; S2. Add phosphonic acid-modified carbon nanotubes and thioacetamide into pure water, add metal nitrate after ultrasonic stirring, raise the temperature to 80-90°C, stir at constant temperature for 8-10 hours, cool to room temperature, filter, wash and dry to obtain modified carbon nanotubes.

2. The tear-resistant fluororubber material according to claim 1, characterized in that: The usage ratio of 2-phosphonobutane-1,2,4-tricarboxylic acid and multi-walled carbon nanotubes in S1 is 1L:20-30g.

3. The tear-resistant fluororubber material according to claim 1, characterized in that: The usage ratio of pure water, phosphonic acid-modified carbon nanotubes, thioacetamide and metal nitrate in S2 is 200 mL: 20 g: 1.5 g: 5.5-6.0 g.

4. The tear-resistant fluororubber material according to claim 1, characterized in that: The metal nitrate is one of zinc nitrate, aluminum nitrate and magnesium nitrate.

5. The tear-resistant fluororubber material according to claim 1, characterized in that: The vulcanizing agent is bisphenol AF or dicumyl peroxide.

6. The tear-resistant fluororubber material according to claim 1, characterized in that: The accelerator is benzyltriphenylphosphonium chloride.

7. The tear-resistant fluororubber material according to claim 1, characterized in that: The plasticizer is one of dibutyl phthalate, dioctyl adipate and tricresyl phosphate.

8. The tear-resistant fluororubber material according to claim 1, characterized in that: The antioxidant is one of antioxidant 6PPD, antioxidant TMQ and antioxidant IPPD.

9. A method for preparing a tear-resistant fluororubber material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Weigh the raw materials according to the mass proportion, and then set the roller temperature of the open mill to 45-50°C. After the temperature is raised, place the tetrapropylene fluororubber in the open mill for plasticization for 3-4 minutes. After the temperature is raised, add the modified carbon nanotubes, vulcanizer, accelerator, plasticizer and antioxidant to the open mill. After the addition is completed, after the rubber material is completely powdered, cut the rubber on the left and right sides for 4-5 times, then make triangle packages 2-4 times in turn, then roll it 2-4 times, and then thin it 4-5 times. After the completion, discharge the material to obtain a mixed rubber, and then place the mixed rubber on a flat vulcanizer for a first-stage vulcanization to obtain a film, and then transfer the film to an aging box for a second-stage vulcanization. After the second-stage vulcanization is completed, take it out and cool it to room temperature to obtain a tear-resistant fluororubber material.

10. The method for preparing a tear-resistant fluororubber material according to claim 9, characterized in that: The vulcanization conditions of the first stage vulcanization are 175-177° C. / 15 MPa×20 min; and the vulcanization conditions of the second stage vulcanization are 200-210° C.×4 h.

Citation Information

Patent Citations

  • Tear-resistant fluoro-rubber mixed compound and preparation method thereof

    CN105218986A

  • Terafluoroethylene-propylene rubber composition resistant to hydrogen sulfide corrosion and application thereof

    CN110157124A

  • Anti-aging and chemical-corrosion-resistant charging pile cable material and preparation method thereof

    CN114672115A

  • Metal oxide-based carbon nanotube composite material as well as preparation method and application thereof

    CN118851836A

  • Fireproof fluororubber for sealing and preparation method thereof

    CN118931073A

Cited By

  • High-temperature-resistant fluororubber material for sealing element and preparation method thereof

    CN121108658A

  • High-temperature-resistant fluororubber material for seals and preparation method thereof

    CN121108658B